Application Of Mirror Therapy On Upper Extremity Motor Recovery In Post-Stroke Patients - Roh Hastuti Prasetyaningsih; Hendri Kurniawan (Poltekkes Kemenkes Surakarta, 2021)
Background: Stroke is a health problem for both developed and developing countries, including Indonesia. Paralysis in stroke is mainly due to damage to the internal capsule. This damage requires neuroplasticity involving a number of parts of the brain to restore. One therapy that is beneficial for neuroplasticity is Mirror Therapy (MT). MT is a rehabilitation tool that aims to restore some of the pathological conditions in which the body representation is affected, including post-stroke motor impairment. Methods: This research is a quantitative pre-experimental design with the type one group pretest-postest. The research subjects were 15 post-stroke patients in residency of Semarang. Research data were collected in August-September 2020. Sample selection with purposive sampling technique who conform inclusion criteria. The Fulg-Meyer Upper Extremity Assessment (FMA-UE) as an aoutcame measure that be avowed valid and reliabel. Data analysis using Paired Sample T-Test because of normally distributed. Results: Statistically the results represent a significant difference in the UE motor ability of post-stroke patients between baseline and after mirror therapy intervention, with a mean difference (5,14) and p value = 0.000 (ρ < 0,05). Application of MT effect on upper extremity motor recovery in post-stroke patients. Conclusions: MT program is an effective intervention for UE motor recovery and motor function improvement in post- stroke patients. MT program can be used as a standardized of hand rehabilitation intervention in hospital, clinics and homes.